2019
DOI: 10.1111/jerd.12548
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and color stability of surface sealants and adhesive systems applied over a resin‐based composite

Abstract: Objective: To evaluate coating materials regarding color and roughness changes when applied over a composite resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The amount of color changes of Optiglaze and control groups were not statistically different. Therefore, Optiglaze sealant had no significant effect on the color stability of the resin composites used, supporting the results of Cortopassi et al who applied different surface sealants to the same type of composite samples and concluded that, the surface sealant application did not provide any benefit in terms of color stability [42]. Nanofillers in Optiglaze might have contributed to the surface discoloration in terms of this outcome as long as the debonding of inorganic fillers form the resin matrix might have formed void formations on surface and incresed the surface roughness [28].…”
Section: Assessment Of the Surface Sealantssupporting
confidence: 77%
“…The amount of color changes of Optiglaze and control groups were not statistically different. Therefore, Optiglaze sealant had no significant effect on the color stability of the resin composites used, supporting the results of Cortopassi et al who applied different surface sealants to the same type of composite samples and concluded that, the surface sealant application did not provide any benefit in terms of color stability [42]. Nanofillers in Optiglaze might have contributed to the surface discoloration in terms of this outcome as long as the debonding of inorganic fillers form the resin matrix might have formed void formations on surface and incresed the surface roughness [28].…”
Section: Assessment Of the Surface Sealantssupporting
confidence: 77%
“…The resin matrix monomers are hydrophilic and contain hydroxyl groups that form bonds with water molecules. This makes the resin matrix monomers absorb the liquid around them and increase the color change in the composite resin restoration [8], [18]. Only 55 respondents (55%) answered the question correctly because professional program students had not yet had knowledge regarding resin matrix monomers at the comprehension level.…”
Section: Resultsmentioning
confidence: 99%
“…The resin matrix has properties that can absorb the liquid. The water absorption that happens causes the composite resin to change color [8]. The higher amount of filler results in better color stability of the composite resin [9].…”
Section: Introductionmentioning
confidence: 99%
“…11 The effects of coating resin on the mechanical properties of GICs have been previously reported [12][13][14] but the studies on the effect of coating resin application on the coloration mainly remained limited to the composite resins. [15][16][17] This study aimed to evaluation of the color stability of coated and uncoated 4 different GICbased restorative materials after immersed in various staining solutions. The null hypotheses were (1) GIC type has no effect on color stability;…”
Section: Introductionmentioning
confidence: 99%